Artificial intelligence(AI) in business and economics research: trends and future - Yap, Jee Yan (2023)
This study aims to investigate the future and trends of Artificial Intelligence in business and economics. The aim of this study is to enhance the level of understanding about the artificial intelligence’s changes to the business and economy. Besides, the methodology used for this study is primary data by distributing survey questionnaires via online and Google form. In addition, a total of 141 questionnaires are distributed to Malaysian citizens who aged between 18-54 years old. All data collected are being analysed through Statistical Package for Social Science (SPSS). SPSS is deployed to perform data analysis such as descriptive analysis, reliability analysis and inferential analysis. While under inferential analysis, it consists of Pearson Correlation Analysis, Multi Regression Model, Independent sample t-Test, and ANOVA test. The findings indicate that government factors, and psychological distress have a significant relationship towards the artificial intelligence’s changes to business and economy. The four IVs in this research had shown significant result .